The automatic generation of childrens stories from a multi-scene input picture - Ang, Karen; Antonio, Janine; Sanchez, Dan.; Yu, Sherie
For children, the act of telling stories develops their language and literacy skills. With this in mind, the Picture Books story generation system was developed to produce childrens stories from a single-scene input picture comprising of the elements (i.e, characters and objects) that were provided by a child, to impart the picture stories have textual counterparts. However, this may result in the production of stories wherein the flow of events do not necessarily match the actual idea of the child when he/she conceptualized the picture story, since the system randomly selects from a predefined list of themes associated with the selected background. Because people tell stories as a sequence of events to share their daily activities and experiences, Picture Books 2 has been developed to provide an environment where a child can creatively define a sequences of scenes depicting the flow of major events in his her target story. The task of the story planner then is to figure out how to connect this sequence of scenes to form a single coherent and interesting storyline of the fable form for children age 6-8 year old.
Keywords: Story generation; Semantic ontology; Storytelling